2020
DOI: 10.1021/acsnano.0c01919
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid–Solid Growth and Optoelectronics of Gallium Sulfide van der Waals Nanowires

Abstract: Nanowires of layered van der Waals (vdW) crystals are of interest due to structural characteristics and emerging properties that have no equivalent in conventional 3D crystalline nanostructures. Here, vapor−liquid−solid growth, optoelectronics, and photonics of GaS vdW nanowires are studied. Electron microscopy and diffraction demonstrate the formation of high-quality layered nanostructures with different vdW layer orientation. GaS nanowires with vdW stacking perpendicular to the wire axis have ribbon-like mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…In accordance with this knowledge, we note that the type A nanowires observed in this work generally exhibited "tapered oscillatory" morphology, suggesting that the original {1010} sidewalls are multi-faceted into other planes [49]. Moreover, the nanowire is possibly rotated by multiples of 30 • around the nanowire axis across the transverse twin boundaries, which is frequently observed from the van der Waals type of nanostructures [31], and thereby yielding the emergence of secondary surface such as (1120) plane. Conversely, the [1210]-oriented type B nanowires displayed (1120) and (0001) sidewalls, as previously reported [32].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with this knowledge, we note that the type A nanowires observed in this work generally exhibited "tapered oscillatory" morphology, suggesting that the original {1010} sidewalls are multi-faceted into other planes [49]. Moreover, the nanowire is possibly rotated by multiples of 30 • around the nanowire axis across the transverse twin boundaries, which is frequently observed from the van der Waals type of nanostructures [31], and thereby yielding the emergence of secondary surface such as (1120) plane. Conversely, the [1210]-oriented type B nanowires displayed (1120) and (0001) sidewalls, as previously reported [32].…”
Section: Resultssupporting
confidence: 87%
“…[23][24][25][26][27]. Recently, the application of VLS mechanism has been extended to the low-dimensional growth of other material systems, specifically layered semiconductors such as transition metal dichalcogenides (TMDs) [28,29], group IV chalcogenides [30,31], and metal halides [32,33]. Eda et al reported the growth of twodimensional (2D) molybdenum disulfide (MoS 2 ) nanoribbons via the VLS method using molten Na-Mo-O droplet particles as the catalyst for crawling growth on the substrate [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the growth of layered nanowires, the VLS catalyst defines the stacking of layers, which can be longitudinal, that is, with layer stacking along the wire axis, [15] or transverse, that is, ribbon-like with layers aligned along the wire axis. [3] Modifications of the catalyst have been shown to yield intermediate morphologies with tilted vdWs layering. [19] While posing significant synthesis challenges, ultrathin 3D-crystalline semiconductor nanowires have been realized for a variety of materials, including Si, [20,21] Ge, [22][23][24] ZnS, [25] CsPbBr 3 , [26] Bi 2 S 3 , [27] GaSb, [28] ZnSe, [29] InAs, [30] Ga 2 O 3 , [31] Mo 6 Te 6 , [32] etc., where they displayed size-dependent properties substantially different from their thicker counterparts such as different crystal orientations, [20,28] absence of defects such as stacking faults or twins, [30] strong quantum confinement, [21,26,33,34] large anisotropic lattice expansion, [25] intrinsic room temperature ferromagnetism, [25] unusually high thermal conductivity, [35] etc.…”
mentioning
confidence: 99%
“…Similar morphologies are observed in layered gallium sulfide (GaS) nanoribbons. [ 20 ] High‐resolution TEM (Figure 2c) in planar horizontal sections shows contrast consistent with basal‐plane oriented monocrystalline GeS, as shown schematically in Figure 1c. Energy‐dispersive X‐ray spectroscopy (EDS) in TEM, however, detects Ge, S, as well as Sn in the van der Waals nanoribbons, i.e., they consist of a Ge 1– x Sn x S alloy rather than pure GeS (Figure 2d).…”
Section: Figurementioning
confidence: 83%
“…In conclusion, we have discussed CL measurements with nanometer‐scale excitation in STEM applied to twisted nanoribbons consisting of Ge 1– x Sn x S, a new class of van der Waals alloys that support propagating excitonic modes and can serve as infrared waveguides. Nanoribbons of wide‐bandgap van der Waals semiconductors, such as GaS, [ 20 ] could extend the operating range to the visible spectrum. The demonstrated approach for probing guided modes at the nanoscale could be extended all the way to the monolayer limit and to complex geometries, such as folded 3D structures [ 27 ] from 2D semiconductors.…”
Section: Figurementioning
confidence: 99%